The band and slough technique is effective for management of diminutive type 1 gastric and duodenal neuroendocrine tumors - Hawa, Fadi; Sako, Zeyad; Nguyen, Than; Catanzaro, Andrew T.; Zolotarevsky, Eugene; Bartley, Angela N.; Gunaratnam, Naresh T. (Endoscopy International Open, 2020)
Background and study aims Endoscopic resection is recommended as initial treatment for early-stage gastric and duodenal neuroendocrine tumors (G-NETs and D-NETs). However, it can cause serious adverse events. We aimed to evaluate the efficacy and safety of the band and slough (BAS) technique as a novel and less aggressive endoscopic therapy for management of such tumors.Four patients, three diagnosed with < 10-mm D-NET and one with 10-mm type I G-NET, were treated with the BAS technique without endoscopic resection. Initial follow-up endoscopy at 3 months was done to assess for residual tumor. Subsequent endoscopic surveillance was performed. After one session of banding, all patients achieved complete remission at 3-month follow-up. No tumor recurrence was detected on repeat biopsy at 12-month surveillance endoscopy. None of the patients developed any adverse events including bleeding or perforation.The BAS technique may prove to be a safe and effective endoscopic therapy for diminutive, non-metastatic type 1 G-NETs and D-NETs. Studies of larger scale and longer follow-up periods are needed to corroborate these findings.